Additive Damages, Fat-Tailed Climate Dynamics, and Uncertain Discounting - Martin L. Weitzman (Kiel Institute for the World Economy (IfW), 2009)
This paper in applied theory argues that there is a loose chain of reasoning connecting the following three basic links in the economics of climate change: 1) additive damages may be more appropriate for analyzing the impacts of global warming than multiplicative damages; 2) an uncertain feedback-forcing coefficient, which might be near one with infinitesimal probability, can cause the distribution of the future time trajectory of global temperatures to have fat tails and a high variance; 3) when highvariance additive damages are discounted at an uncertain rate of pure time preference, which might be near zero with infinitesimal probability, it can make expected present discounted disutility very large. Some possible implications for welfare analysis and climate-change policy are briefly noted.
Keywords: 330; Climate change; fat tails; Klimaveränderung; Soziale Kosten; Soziale Diskontrate; Risiko; Statistische Verteilung; Theorie